Acupressure Therapy for Chronic Pain in Elderly Patient with Hypertension Stage II: A Case Study - Mukaromah, Afifatul; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2024)
In the aging process, various changes occur regarding biology, cognition, and psychosocial life. The elderly are easily affected by diseases such as non-communicable (degenerative) diseases such as hypertension. As a result of aging, it can reduce the elasticity of the blood vessel walls and cause stiffness in the blood vessels; as a result, blood pressure in the elderly tends to increase. This study aims to determine the impact of applying acupressure therapy to chronic pain problems in the elderly. The research method used in this study was a descriptive case study. The research was conducted for five days on one patient with hypertension and chronic pain at an Elderly Residential Home. Acupressure therapy was carried out once a day for 20 minutes. Evaluation of the implementation is given using the NRS pain scale. The result of Acupressure therapy showed that the level of chronic pain was decreased from the NRS scale 5 to the NRS scale 2, blood pressure 140/80 mmHg, pulse rate 85 x/minutes, respiration rate 18 times per minute, and SpO2 96. This study recommends that acupressure therapy can be applied to treat chronic pain in hypertension patients as a complementary therapy.